Investigation of Engineering Properties and Solidification Mechanism of Loess by Sodium Silicate Alkali-Activated Coal Gangue Powder - Yang Yang; Shengsheng Yu; Xiao Ma; Aiping Hu; Ping Li (Advances in Civil Engineering)
The aim of this study is to investigate the engineering properties and solidification mechanism of loess through the use of alkali-activated coal gangue powder with sodium silicate. Experimental methods and comprehensive analysis were employed to examine the effects of different proportions of alkali-activated coal gangue powder with sodium silicate on the engineering properties of loess, including mass shrinkage, compressibility, and shear strength. Additionally, scanning electron microscopy was utilized to gain in-depth insights into the interaction and solidification mechanism between loess and alkali-activated coal gangue powder. The results show that the sodium silicate alkali-activated gangue powder curing loess has significantly improved the compressive strength and shear strength of the loess. With a ratio of 7 : 2 : 1, the 28 days compressive strength of solidified loess is 1.7 MPa, and the shear strength is 67.92 kPa, which is 1.91 and 2.13 times the 28 days compressive strength and shear strength of unmixed gangue powder and sodium silicate specimens respectively. The hydration–hydrolysis reaction, ion-exchange reaction, and volcanic ash reaction of the gangue powder under an alkaline environment generated hydrides that filled the pores between soil particles, enhanced the interparticle cohesion, and made the internal structure of the specimens denser, improving the engineering performance of loess solidification. The proposed sodium silicate alkali-activated gangue powder curing loess mechanism can provide a theoretical reference for the engineering application of gangue powder and the curing modification of loess.